Anisotropy development during HDPE necking studied at the microscale with in situ continuous 1D SAXS scans. Issue 2 (12th October 2017) - Farge, Laurent; Boisse, Julien; Bihannic, Isabelle; Diaz, Ana; André, Stéphane
ABSTRACT: To improve our understanding of the rheology of solid semi‐crystalline polymers, descriptions of the deformation‐induced microstructural reorganization mechanisms with precise and local quantitative data are needed. The novel results presented in this paper for high‐density polyethylene (HDPE) were obtained in situ on a coherent synchrotron beamline specifically developed to allow very fast scanning of a specimen under tensile test. From the recorded small angle X‐ray scattering (SAXS) patterns, a quantitative index characterizing the microstructure local anisotropy was calculated. With the scanning operating mode, many different material points could be studied. These material points were subjected to various deformation paths in the plastic regime due to the necking development and its propagation. Their positions and strain evolutions were obtained through digital image correlation (DIC). With an appropriate analysis coupling the bulk‐averaged SAXS and DIC surface measurements, the microstructural anisotropy index is shown to have a given value at a given true strain. This means that the microstructure morphology is only governed by the current strain level. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2018, 56, 170–181 Abstract : Because of necking, the different material points of a semi‐crystalline specimen subjected to tensile deformation undergo various loading paths. By performing 3D digital image correlation and in situ scanning small angle X‐Ray scattering measurements, the strain and microstructure evolutions of all the material points of an HDPE specimen were studied. The microstructure state of a given material point exclusively depends on the current strain level and not on the specific loading history of the considered point.